A new Iberian species of Chevrolatia Jacquelin du Val (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Among previously known Palaearctic species of Chevrolatia Jacquelin du Val, adults of only two have unmodified male protrochanters. Another species showing this character is described, Chevrolatia iberica sp. n., based on a specimen collected in the Spanish province of Alicante. It differs from its two sympatric congeners, C. hispanica Franz and C. sylvanica Hernando & Castro, in a combination of conspicuously short apical projections of the aedeagus, a strongly curved median lobe, a short capsular component of the endophallus, and the parameral setae of subequal length and sparsely, evenly distributed.